Larus genei BREME, 1839: Prima segnalazione di nidificazione in Laguna di Venezia (Aves, Charadriiformes, Laridae) - Marco Picone; Marco Basso; Fabio Berton; Lucio Panzarin (2023)
Twelve pairs of nesting Slender-billed gull were observed in Valle Sacchetta (Saccagnana, municipality of Cavallino-Treporti) in a mixed colony with Mediterranean gull (Larus melanocephalus), Black-headed gull (Larus ridibundus), Common tern (Sterna hirundo), and Sandwich tern (Thalasseus sandvicensis). The settling was observed in an elevated salt marsh with spare halophilous vegetation cover (Sarcocornia fruticosa and Limonium narbonense).